An eclectic review on dicarboxylic acid production through yeast cell factories and its industrial prominence - Kayalvizhi, Ramalingam; Sanjana, Jayacumar; Jacob, Samuel; Kumar, Vinod (Springer, 2024)
Dicarboxylic acid (DCA) is a multifaceted chemical intermediate, recoursed to produce many industrially important products such as adhesives, plasticizers, lubricants, polymers, etc. To bypass the shortcomings of the chemical methods of synthesis of DCA and to reduce fossil fuel footprints, bio-based synthesis is gaining attention. In pursuit of an eco-friendly sustainable alternative method of DCA production, microbial cell factories, and renewable organic resources are gaining popularity. Among the plethora of microbial communities, yeast is being favored industrially compared to bacterial fermentation due to its hyperosmotic and low pH tolerance and flexibility for gene manipulations. By application of rapidly evolving genetic manipulation techniques, the bio-based DCA production could be made more precise and economical. To bridge the gap between supply and demand of DCA, many strategies are employed to improve the fermentation. This review briefly outlines the advancements in DCA production using yeast cell factories with the exemplification of strain improvement strategies.
Keywords: Bioproduction; Dicarboxylic acid; Genetic manipulation; Green manufacturing; Yeast cell factories